Kinetic Study and Mechanism of Mono-β-Naphthylamine Phosphate (Ba-Salt) via Conjugate Acid Species - Patil, R.; Shinde, C.P.; Samadhiya, A.; Das, K.B. (Asian Journal of Chemistry, 2010)
Hydrolysis of mono-β-naphthylamine phosphate (Ba-salt) was carried out in the acid region (0.1-7.0 mol dm–3) at 98ºC in aqueous media. The acid log rate profile has a rate maxima at 4.0 mol dm–3. Here mainly contribution of mono-β-naphthylamine phosphate (Ba-salt) is involved in hydrolysis. The participation of conjugate acid species and determination of theoretical rates has been exhibited by ionic strength data. The observed rates were also found in close agreement with the estimated theoretical rates derived from the 2nd empirical term of Debye-Hückel equation. By molecularity data the bimolecular nature of reaction is detected and P-N bond fission has been stengthened by isokinetic relationship.